Carreira no esporte: trajetórias de vida de atletas paralímpicos - Siqueira, Rafaela Fernanda Barbosa de (2019)
This work was carried out with the main objective of understanding the career of former athletes Brazilian Paralympic, through elements of their life trajectory. In order to achieve this, the following specific objectives were pursued: contextualizing Paralympic sport in Brazil, identifying aspects of the objective career dimension, knowing aspects of the subjective career dimension, finally, understanding the impact of sport on their lives and life from other people. Career is understood as a phenomenon composed by the objective and subjective dimensions that are interrelated, observing, in the case of this study, issues involving people with disabilities, work and sports. The research was conducted using a qualitative method in which the narrative interview was chosen as technique of data collection. Interviews were conducted with six former athletes Brazilian Paralympic, along with documentary research on Paralympic sport. The qualitative nature of the research made possible the treatment of the data by analysis of thematic content. By knowing aspects of objective career dimension in the Paralympic sport, it was understood that there is no predetermined structure formally described to develop as a Paralympic athlete. However, there is an expectation as to the performance of athletes, wherein the maximum possible should be reached for participation in world competitions and good placements in these competitions. Regarding aspects of the subjective career dimension, the sport as a possibility for professional development, from the perception of the athletes had got that from the insertion in the high levels of competition. In other words, with the individual progression, even if it did not mean, initially, financial returns. In addition, the career was perceived by the research subjects as personal, physical, cultural and interpersonal development, providing reflection on themselves, but also allows others to reflect and re-evaluate their perceptions and expectations about them. However, career in sport can also be a source of insecurity, since time as an athlete and financial return are marked by uncertainty. As recommendations for future research, the investigation of the career of athletes or former athletes Paralympic with acquired disabilities presents with potential, as it would allow understanding both their peculiarities and their approximations with the present research. The choice of athletes or former athletes Paralympic of collective sports can also contribute to the studies on careers, since it would also allow knowing this reality. The reflections of this research contribute to studies in the area of Organizations, Management and Society, seeking to broaden the understanding of career management in the social context and, consequently, the dynamics and broader relations that involve them.